International Trade, Trade and Industrial Policy and Imperfect Competition: A Survey. - Venables, A (CEPR, 1985)
The incorporation of details of industrial organisation into the study of international trade has been the subject of a fast growing recent literature which is surveyed in this paper. Whereas the conventional theory of trade deals almost exclusively with perfect competition and non-increasing returns to scale, the new literature models imperfect competition, increasing returns to scale and product differentiation. In Section 2, I discuss how adding imperfect competition to trade theory generates new insights for our understanding of such phenomena as intra-industry trade. With imperfect competition and increasing returns to scale, trade may affect welfare by changing the degree of competition, firm scale, and the number of product varieties available in an economy. Section 3 of the paper examines the extent to which free trade achieves these potential gains from trade under a variety of different types of competition and market structure. In the presence of imperfect competition there is generally scope for the active use of policy to raise welfare through changes in the terms of trade or by correcting distortions in the domestic economy. Sections 4 and 5 discuss the roles of both commercial and industrial policy, and show that the effects of policy are quite sensitive to the type of competition and market structure in the industry under study. Section 6 discusses the effects of one country's policy on other countries, and the role of coordinated commercial and industrial policy.